A Simple Protocol for Managing Post-Operative Urinary Retention (POUR): An Experience and Evidence - Fakhrizal, Edy; Maryuni, Sri Wahyu; Koerslo, Hamka; Novri, Dhini Aiyulie; Yuda, Dika Putra (GLOBAL HEALTH SCIENCE GROUP, 2024)
Proposing a simple protocol in the management of urinary retention in postoperative patients that can provide promising results. Methods: We analyzed women who underwent pelvic organ prolapse surgery for 6 years from January 2018 to July 2023. The incidence of postoperative urinary retention was identified and we implemented a simple protocol and assessed its success rate.Result : There were 503 surgeries due to POP incidence in Arifin Achmad General Hospital, Riau Province - Indonesia for 6 years. One hundred sixteen cases (23 %) experienced POUR, with mean first residual urine was about 393 ml (110–1.200 ml). The protocol was applied, and 81 % cases revealed satisfying results. In successful group, the patients were discharged after 4±1 days. There were significant differences in the first residual urine between patients who were successfully treated with the simple protocol (350±227 ml) and patients requiring physiotherapy consultation (576±325 ml), with p = 0.005. Conclusion: Most cases of postoperative urinary retention can be managed using this protocol. So this protocol can be considered to be applied.